Experimental Investigation on the Ballistic Resistance of Aluminium Plate under High Velocity Impact / Mohd Rozaiman Aziz ...[et al.] - Aziz, Mohd Rozaiman; Kuntjoro, Wahyu; Natarajan, Valliyappan David (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Ballistic resistance has become towards researchers’ attention especially those in enforcement industry. In the ballistic resistance, researchers are keen to determine the lowest velocity of projectile that able to perforate a target. From result obtained, researchers can propose modification to enhance the survival of enforcement personnel. For an example, armor shield which is employed by enforcement personnel during gun fight. The main objective of this paper was to present the preliminary result of ballistic resistance of aluminium plate that will be used as a reference in the experiment works later. Future works will involve aluminium laminated with z-composite. In this study, the target was aluminium plate with thickness of 3 mm and fragment simulating projectile (FSP) acted as the projectile. The FSP was launched from gas gun which was located 2 meters from the aluminium plate. The velocity of FSP was varied by changing the charge weight. The experiment was carried-out at Science and Technology Research Institute for Defence (STRIDE), Batu Arang. From the experiment conducted, it was found the ballistic limit was equal to 257.7 m/s. Furthermore, there were two main modes of failure observed which were non-perforation and successful perforation. For non-perforation, the mode of failure was crater with and without FSP embedded into the plate. Meanwhile for the successful perforation, the mode of failure was a hole along with petals.